AN ANALYSIS OF PREPOSITION ERRORS: The Case of in, on, and at - Suzanne, Nina (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2017)
The use of correct preposition can influence the quality of information in spoken language. However, errors often occur in the use of prepositions, especially, in, on, and at. This research was done to identify the preposition errors made by students when speaking English. The data were obtained from the interview transcription which was used as the source of data from the research done in 2005 by the writer herself about grammatical and diction errors made by the first-year students of SMAN 2 Padang when speaking English. The finding showed that errors in the use of preposition in and at occurred more often than errors in the use of preposition on. The errors are included into two kinds of errors, namely misformation errors (substitution of â€œinâ€ for â€œatâ€, â€œinâ€ for â€œonâ€, â€œinâ€ for â€œfromâ€, â€œatâ€ for â€œtoâ€ and â€œatâ€ for â€œinâ€) and addition errors (addition of â€œinâ€ and â€œatâ€). The finding also proved that the occurrence of errors in the use of prepositions in spoken English language is influenced by the speakersâ€™ first or second language.Key words: preposition errors; preposition in, on, and at; error analysis; spoken languageÂ  ANALISIS ERROR DALAM PENGGUNAAN PREPOSISI:Kasus pada Preposisi in, on, dan atAbstrakÂ Â Â Â Â Â Â Â Â Penggunaan preposisi yang tepat dapat mempengaruhi kualitas informasi yang diberikan dalam bahasa lisan. Namun, error sering muncul dalam penggunaan preposisi tersebut, khususnya untuk preposisi in, on, dan at. Penelitian ini bertujuan untuk mengidentifikasi apa saja error yang dibuat oleh siswa dalam berbahasa Inggris. Data diperoleh dari transkripsi wawancara yang merupakan sumber data dari penelitian yang dilakukan oleh penulis sendiri pada tahun 2005 mengenai error dalam penggunaan preposisi dan diksi oleh siswa kelas satu SMAN 2 Padang ketika berbicara dalam bahasa Inggris. Temuan memperlihatkan bahwa error dalam penggunaan preposisi in dan at lebih sering muncul daripada error dalam penggunaan preposisi on. Error tersebut dikategorikan ke dalam dua jenis error yaitu misformation dan addition. Hasil penelitian juga membuktikan bahwa munculnya error dalam penggunaan preposisi ketika berbahasa Inggris dipengaruhi oleh bahasa ibu atau bahasa kedua siswa.Kata kunci: error dalam penggunaan preposisi; preposisi in, on, dan at; analisis error; bahasa lisan